PENGARUH LOKASI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI INDOMARET PT. INDOMARCO PRISMATAMA CABANG BOGOR - Lulu Zakia; Jaenuddin (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine whether there is an influence between location and promotion on purchasing decisions at PT Indomarco Prismatama Bogor Branch. The method used is associative research with a quantitative approach. In sampling used the Slovin formula and obtained 100 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, coefficient of determination analysis and hypothesis testing. The results of this study are location and promotion have a significant effect on purchasing decisions with the regression equation Y = 7.036 + 0.178 X1 + 0.406 X2. The coefficient of determination is 58.4% while the remaining 41.6% is influenced by other factors. Hypothesis testing obtained the value of F count> F table or (68.067> 3.09). Thus Ho is rejected and H3 is accepted. This means that there is a simultaneous significant influence between location and promotion on purchasing decisions at PT. Indomarco prismatama Bogor Branch.